Environment, Culture and Diffusion : The Broad Bean in Québec - Gade, Daniel (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1994)
An ancient Old World domesticate, broad bean [Vicia faba) was carried from Europe to North America early in the seventeenth century. Competition and unfavorable growing conditions marginalized it over most of the United States and Canada. The major exception was the Saguenay—Lac-Saint-Jean region where gourgane acquired a horticultural and culinary role. However, its cultivation there is not an archaic survival of old French varieties and usages. This study poses larger questions about the interplay of agro-ecological fit and cultural factors in the intercontinental transfer of crops.